Pengaruh Tingkat Religiusitas Terhadap Kompetensi Interpersonal Siswa Madrasah Aliyah - Jauharuddin, Ahmad (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2020)
Interpersonal competence plays an important role in creating effective and positive relationship patterns, especially in adolescent life. As a phase that requires a broader social environment, it is not uncommon for adolescents at the high school level to be confronted with problems that hinder their social development such as student brawl, motorcycle gang delinquency, bullying behavior towards fellow students. This study aims to determine the effect of the level of religiosity on interpersonal competence. The study used a quantitative approach with multiple regression methods, the study population was students of Madrasah Aliyah Al-khairiyah Karang Tengah with a total sample of 120 students. The sampling technique uses simple random sampling with a measure of religiosity using the GSS (General Social Survey) and interpersonal competency using an ICQ (Interpersonal Competence Quesionaeri) measurement tool. The results of statistical analysis revealed that the acquisition of R Square amounted to 0.075 ability to initiate, 0.053 ability to be assertive, 0.136 ability to open up 0.077, ability to provide emotional support 0.072 ability to overcome conflict. The F-test results of 0.00 showed that there was a significant influence on the level of religiosity on adolescent interpersonal competence.